The Corruption of Ethics in Higher Education - Heyneman, Stephen (International Higher Education, 2011)
Universities can be corrupt through the abuse of authority for both personal and material gain. In order to reduce corruption, quality assurance mechanisms might include anti-corruption evidence as a criterion for accreditation. Another implication is that development assistance agencies that make investments in higher education, may have to consider the level of corruption when making those investments.